A Review of the application of robots in maxillofacial surgery - Arian, Yeganeh (Eximia, 2022)
Aim: The purpose of this study was to review new articles on the use of robotic surgery in maxillofacial surgery. Method & Materials : For the purpose of this review study, all Medline (Pubmed), Google scholar electronic resources focused on the use of robotic surgery in maxillofacial surgery in the period 1999-2021 were reviewed . Results : Using robots in maxillofacial surgery can reduce hospitalization time, reduce intraoperative bleeding, and improve recovery for patients, although the high cost and lack of touch can be a problem. noCsulcnoC: The results of this review study show that the surgery robot can replace open surgical methods of maxillofacial surgery. Although it may not be generalized for use, patients may be assisted in areas where the surgeon may not be present.